PERAN MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR NGAJI ANAK DI LINGKUNGAN PEDESAAN CIKALONG RW 06 - Siti Sarah Nur Fatahilah; Intan Rustianti; Rafli Dzikruloh; Dadang Rohmansyah; Nurhani Chomsangadah; Asep Dadan Pirumansyah; Intan Dini Hermawan; Eka Martiani; Maryati Maryati; Fahri Ali Maulana; Rahmat Nur Ramdan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2026)
Islamic education plays a significant role in developing children's religious character and improving their ability to read the Qur'an, particularly in rural areas that still face limitations in educational facilities and low learning motivation in Qur'anic studies. Therefore, effective and well-organized educational management is needed to create a structured and sustainable learning process that meets students' needs. This study aims to identify and analyze the role of Islamic education management in increasing children's motivation to learn Qur'anic reading in the rural area of Cikalong RW 06. The research employed a qualitative descriptive method with a participatory approach, conducted through observation, interviews, and the direct implementation of Qur'anic learning programs for children. The findings indicate that the application of Islamic education management, which includes planning learning activities, organizing programs, implementing varied and engaging teaching methods, and conducting regular evaluations, has a positive impact on improving students' learning motivation, attendance, and participation in Qur'anic learning activities. In conclusion, well-planned and continuous Islamic education management, supported by the involvement of parents and the community, can effectively enhance children's enthusiasm for learning the Qur'an and foster the development of their religious character in rural environments.